Phytoplankton diversity and abundance in coastal waters of Carigara Bay, Leyte, Philippines during the Pyrodinium bloomin 2017. - Malacura, Alessandra M. (Alessandra M. Malacura, 2018)
The study reports the abundance of Pyrodinium bahamense and other phytoplankton species in Carigara Bay during red tide bans in the months of September to December 2017. Samples were collected from three sampling stations monthly within this period. For qualitative analysis, three replicates of 50 mL of samples were obtained using a 20 um mesh size plankton net. For quantitative analysis, three 1 L samples were collected using the bucket method. Physico-chemical parameters were measured in situ for temperature, salinity, transparency, depth, light intensity, current velocity, and pH; while Total Suspended Solids, nutrient and chlorophyll-a concentration were analyzed in the laboratory. A total of 45 genera of phytoplankton were identified. The Paralytic Shellfish Poisoning (PSP) causing agent, Pyrodinium bahamense, was positive in all sampling months and dominated in September with 6.0 x 10 raised to the power of 3 cells/L. The diatom, Thalassiothrix was dominant in October (16 x 10 raised to the power of 3 cells/L) and December (6.3 x 10 raised to the power of 3 cells/L), while Chaetoceros dominated during November (5.2 x 10 raised to the power of 3 cells/L). The average cell density of Pyrodinium bahamense during the sampling period was 1.9 x 10 raised to the power of 3 cells/L. The average total cell density of phytoplankton in Carigara Bay was 27 x 10 raised to the power of 3 cells/L during the whole sampling period. This study can be used in future studies for predicting patterns of Pyrodinium bloom.